EGFR‐TKIs plus local therapy demonstrated survival benefit than EGFR‐TKIs alone in EGFR‐mutant NSCLC patients with oligometastatic or oligoprogressive liver metastases. Issue 10 (8th December 2018) - Jiang, Tao; Chu, Qian; Wang, Huijuan; Zhou, Fei; Gao, Guanghui; Chen, Xiaoxia; Li, Xuefei; Zhao, Chao; Xu, Qinghua; Li, Wei; Wu, Fengying; Xiong, Anwen; et al.
Abstract : To investigate whether addition of local therapy to EGFR‐TKIs could provide survival benefit than EGFR‐TKIs alone in EGFR‐mutant NSCLC patients with oligometastatic or oligoprogressive liver metastases (LM). Patients with EGFR‐mutant NSCLC and oligometastatic or oligoprogressive LM who met inclusion criteria were retrospectively identified. The primary endpoint was progression‐free survival (PFS); secondary endpoints included overall survival (OS) and patterns of failure. Addition of local therapy was associated with a significantly longer PFS (13.8 vs . 8.6 m, p <0.001) and OS (31.2 vs . 18.5 m, p <0.001) in whole group. In oligometastatic cohort, 20 patients received EGFR‐TKIs and 23 received EGFR‐TKIs plus local therapy as first‐line treatment. Addition of local therapy showed a significantly longer PFS (12.9 vs . 7.9 m, p = 0.041) and OS (36.8 vs . 21.3 m, p = 0.034) than EGFR‐TKIs alone. In oligoprogressive cohort, 24 patients received continuation of EGFR‐TKIs plus local therapy and 25 received switching chemotherapy. Median PFS2 (13.9 vs . 9.2 m, p = 0.007) and OS (28.3 vs . 17.1 m, p = 0.011) was significantly longer in combined group than in switching chemotherapy group. Distant metastatic sites progression was the major pattern of failure in combined group while locoregional recurrence was the major reason in monotherapy or switching chemotherapy group. Our study suggested that EGFR‐TKIs plus local therapy showed prolonged survival benefit than EGFR‐TKIs alone in EGFR‐mutant NSCLC patients with oligometastatic or oligoprogressive LM, indicating addition of local therapy would be alternative choice in this clinical scenario. Abstract : What's new? Patients with non‐small cell lung cancer (NSCLC) who develop liver metastases frequently suffer poor prognosis, despite treatment with otherwise highly effective epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs). In the effort to overcome this problem, the authors of this study examined patient outcomes following combined treatment with EGFR‐TKIs and local therapy. A significant improvement in progression‐free survival and overall survival was detected following administration of combined therapy in EGFR‐mutant NSCLC patients with oligometastatic or oligoprogressive liver metastases. The findings suggest that combined local therapy and EGFR‐TKIs could help improve patient outcome in EGFR‐mutant NSCLC with liver metastasis.